Analysing strategic decision-making in an environment with high rates of change : a model for leaders of organisations - Weilert, Heinz Maria (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Information Science))--University of Stellenbosch, 2011.